The rise and decline and rise of China : searching for an organising philosophy. - Du Plessis, Hester (MAPUNGUBWE INSTITUTE FOR, 2016)
With China poised to become a major global power in the 21st century, it is fitting to examine the factors which have contributed to the rise, once again, of this multifaceted country and notable civilization. This publication is the culmination of research undertaken by MISTRA, which set out to investigate the multifaceted factors that accompanied and influenced the evolution of Chinese society over the centuries. While the issue of belief systems, from the Han Dynasty to the current period, are the main areas of focus, an attempt has been made to examine the totality of human endeavours that characterize this evolution. Out of this has emerged a transdisciplinary compendium of separate but related chapters on economic and social life, political institutions and practices, and the interrelationships between these and culture, particularly the philosophy underpinning Confucianism. Indeed, an investigation into civilizational cycles, by necessity of its complexity, requires input from various fields of knowledge and expertise. Running like a red thread through this book are the manifestations of Sino-African relations dating back many centuries. In this way, The Rise and Decline and Rise of China: Searching for an Organising Philosophy takes forward the work MISTRA conducted on the Mapungubwe society, one of the advanced states that existed in southern Africa some 800 years ago, and which enjoyed trade relations with China and other centres in the East. Mapungubwe rose and fell, long before European colonial incursions. Other states emerged in the vicinity, but they also suffered the same fate. When do southern Africa and Africa at large rise again? Are there lessons that the continent can draw from the experience of the Chinese people? If - beyond material considerations - religion, culture and ideology do play a role in the rise, decline and resurgence of a civilization, what are the similarities and contrasts between these regions? Thematic areas covered in the research report include examination of China as a 'civilizational-state', its societal characteristics, complex political structure, success as a state-led economy, and its economic relations with developed and developing regions including Africa--Publisher's website.